2013
DOI: 10.1371/journal.pone.0075102
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Tumor Effect of HDAC Inhibition in a Human Pancreas Cancer Model Is Significantly Improved by the Simultaneous Inhibition of Cyclooxygenase 2

Abstract: Pancreatic ductal adenocarcinoma is the fourth leading cause of cancer death worldwide, with no satisfactory treatment to date. In this study, we tested whether the combined inhibition of cyclooxygenase-2 (COX-2) and class I histone deacetylase (HDAC) may results in a better control of pancreatic ductal adenocarcinoma. The impact of the concomitant HDAC and COX-2 inhibition on cell growth, apoptosis and cell cycle was assessed first in vitro on human pancreas BxPC-3, PANC-1 or CFPAC-1 cells treated with chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 61 publications
1
42
0
Order By: Relevance
“…In this study, we focused on COX-2 and HDAC as therapeutic targets, both of which were highly expressed in high-grade bladder cancer (3, 4, 7). Previously, Peulen and colleagues reported that combined treatment with the HDAC inhibitor MS-275 and the COX-2 inhibitor celecoxib induced G 1 cell-cycle arrest against pancreatic cancer cells in vitro (14). On the other hand, in the present study, the combined treatment with a novel HDAC inhibitor, OBP-801, and celecoxib synergistically inhibited cell growth of high-grade bladder cancer cells in vitro by enhancing apoptosis (Fig.…”
Section: Discussionsupporting
confidence: 47%
“…In this study, we focused on COX-2 and HDAC as therapeutic targets, both of which were highly expressed in high-grade bladder cancer (3, 4, 7). Previously, Peulen and colleagues reported that combined treatment with the HDAC inhibitor MS-275 and the COX-2 inhibitor celecoxib induced G 1 cell-cycle arrest against pancreatic cancer cells in vitro (14). On the other hand, in the present study, the combined treatment with a novel HDAC inhibitor, OBP-801, and celecoxib synergistically inhibited cell growth of high-grade bladder cancer cells in vitro by enhancing apoptosis (Fig.…”
Section: Discussionsupporting
confidence: 47%
“…17 We selected the widely used BxPC-3 cells for their ability to grow on CAM. This anti-tumor growth effect was associated with a massive inhibition of capillaries development within the tumoral stroma, suggesting a loss of proangiogenic activities of the cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In order to visualize the tumor vasculature, tumors sections have been subjected to FITC-conjugated SNA (Sambucus nigra agglutinin) staining as previously described. 17 Densitometric profiling and quantification were performed using ImageJ (Rasband, W.S., ImageJ V1.48, U. S. National Institutes of Health, Bethesda, Maryland, http:// imagej.nih.gov/ij/, 1997-2014).…”
Section: Ultrastructural Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, previously it has been shown that the long-term maintenance in culture of PDAC cell lines, such as BxPC-3, CFPAC-1 and PANC-1 cells 33,34 , resulted in distinct and irreversible loss of crucial genetic and biologic properties. This included the occurrence of distinct stem cell populations and complex genomic aberrations, affecting critical signaling pathways 35,36 .…”
Section: Discussionmentioning
confidence: 99%